2006
DOI: 10.1021/jp065876s
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction and Experimental Evaluation of a Photoinduced Electron-Transfer Sensor

Abstract: An approach is presented for the design of photoinduced electron-transfer-based sensors. The approach relies on the computational and theoretical prediction of electron-transfer kinetics based on Rehm-Weller and Marcus theories. The approach allows evaluation of the photophysical behavior of a prototype fluorescent probe/sensor prior to the synthesis of the molecule. As a proof of concept, a prototype sensor for divalent metal ions is evaluated computationally, synthesized, and then analyzed spectroscopically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 17 publications
4
49
1
Order By: Relevance
“…All the excitons discussed here have an e − -h + distance of more than 2Å, which are different from the excitons generated in, for instance, anthracene [32,33], where the HOMO and LUMO completely overlap and the e − -h + distance is expected to be very small. The current study suggests that the donor molecules MTPAo, MTPAcl, and MTPAc are all promising donor modula for organic photovoltaics, in addition to MTPA and MTPAa that were already being used.…”
Section: Resultscontrasting
confidence: 56%
“…All the excitons discussed here have an e − -h + distance of more than 2Å, which are different from the excitons generated in, for instance, anthracene [32,33], where the HOMO and LUMO completely overlap and the e − -h + distance is expected to be very small. The current study suggests that the donor molecules MTPAo, MTPAcl, and MTPAc are all promising donor modula for organic photovoltaics, in addition to MTPA and MTPAa that were already being used.…”
Section: Resultscontrasting
confidence: 56%
“…The sensor in Fig. 1 differs slightly from the one discussed in the original work1 in that the linker of the current sensor has one more CH 2 . We expect, and as our study has also shown, that this minor difference would not affect any of the computational predictions.…”
Section: Computational Detailsmentioning
confidence: 79%
“…Once the sensor candidates are selected computationally, they will then be synthesized, characterized, and subsequently refined. As a proof of concept, we have successfully developed a PET fluorescent sensor for detecting Zn 2+ using the new approach 1. The computational selection of the sensor candidates in that work is based on the comparison of the energies between the Highest Occupied Molecular Orbital (HOMO) and the Lowest Unoccupied Molecular Orbital (LUMO) of fluorophore, free receptor, and bound receptor using B3LYP/6-31G(d,p).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,16] However, different from most D-π-A fluorophores, [19][20][21][22][23] the emission of the FMRs is not sensitive to the polarity of the solvent, [5] that is, the emission intensity and the emission wavelength will not change significantly by variation in the polarity of the solvents. [5,6,24] According to the traditional theory of FMRs, viscosity sensitivity and polarity sensitivity are two exclusive properties, that is, those rotors that show solvent-polarity-dependent emission will not show the FMR property and vice versa.…”
Section: Introductionmentioning
confidence: 99%